2020
DOI: 10.3390/hydrology7010018
|View full text |Cite
|
Sign up to set email alerts
|

Bottom Sediment Characteristics of a Tropical Lake: Lake Tana, Ethiopia

Abstract: Sediment concentration of rivers in developing countries has been increasing greatly over the last 50 years due to the conversion of forest to continuously cultivated land with the increasing population. Few studies have addressed its effect on sedimentation and water quality of the lakes by analyzing bottom sediment characteristics. In this study, the objective was to investigate the spatial distribution (and their interrelationships) of the bottom sediment characteristics in the largest lake in Ethiopia, Lak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 49 publications
1
22
0
Order By: Relevance
“…Spatially distributed phosphorus concentrations for the lake were published previously by the authors separately. The available phosphorus in sediment was documented in [32] and the dissolved phosphorus was measured by Kibret for his MSc thesis and published as [36].…”
Section: Datasetsmentioning
confidence: 99%
See 1 more Smart Citation
“…Spatially distributed phosphorus concentrations for the lake were published previously by the authors separately. The available phosphorus in sediment was documented in [32] and the dissolved phosphorus was measured by Kibret for his MSc thesis and published as [36].…”
Section: Datasetsmentioning
confidence: 99%
“…The lake is in a transitional stage to eutrophic status [23] and water hyacinths have appeared [24]. Previous studies have addressed the lake water balance [25][26][27], the total sediment mobilized from the upland watersheds [28,29], sediment budgets [30,31], bottom sediment characteristics [32], peninsula development [33,34], dissolved and available phosphorus concentrations in the lake water and bottom sediments [32,35], water quality and status of eutrophication condition [8,23] and acreages of water hyacinths [24,36,37]. However, the relationship between the lake's physical characteristics and water quality has not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Total dissolved phosphorus (TDP) concentrations in the water hyacinth infected areas were as high as 0.45 mg P/l. Kebedew et al (2020a) reported that the average Lake Tana sediment bottom TN concentration was 0.8 g.kg −1, and Olsen available phosphorus was 0.019 g.kg −1 . Tibebe et al (2019) reported nearshore NO 3 -N concentrations ranging from 0.28 to 1.56 mg N/l in the dry phase and 0.58-1.03 mg N/l in the rain phase with the same average concentration of 0.79 mg N/l in both phases.…”
Section: Introductionmentioning
confidence: 99%
“…(3.15 Gg a À1 ) in the last 8000 years and 0.34 mm a À1 over the past 250 thousand years (Roberts et al, 2018). The sediment texture became finer in time and is currently mainly clay (Kebedew et al, 2020). As mentioned in Section 2.2.4, the sediment deposition rates 108 Gg a À1 (Omega, 2012) and 254 Gg a À1 (Belay, 2015) using their bathymetric surveys that were greater than those reported in Table 2 were incorrect because of problems with the benchmark.…”
Section: Discussionmentioning
confidence: 99%
“…In the recent sampling of the bottom sediment in 2018 showed that most of the lake bottom sediment was even finer with 75% of clay, 9% silt and 14% sand. Only near the river inlets is sediment sandier ( Kebedew et al, 2020). These inlets were all sand in the 1930s (Cheesman, 1936).…”
Section: Sediment Depositionmentioning
confidence: 99%